Improvements in the design of the ammonia synthesis process implementing counter current gas permeation modules - Fischer, Carlos Daniel (2012)
This paper explores mass exchanging the outlet and inlet streams of the reactor, following a design heuristic proposed by Fischer and Iribarren in Industrial and Engineering Chemistry Research 2011, 50 (11), 6849−6859 within the Hierarchical Process Design Procedure by J. M. Douglas in Conceptual Design of Chemical Processes, McGraw-Hill, 1988. When applied to the ammonia synthesis process, this design methodology generated a process alternative different from that previously proposed by other authors, resorting to ceramic membrane counter current gas permeation units to perform the mass exchange of hydrogen. This alternative design is shown to produce a reduction of the gas recycle stream (hydrogen and nitrogen) of up to an interesting 8.40%, reducing recompression associated costs. However, as the present cost of zeolite membranes is still high and their hydrogen-nitrogen selectivity moderate, in the optimal economical solution, the net annual income amounted to 4.56%, corresponding to U.S. $817,793/year savings. The heuristic was used again at a later refinement stage, yielding an appreciable percent reduction in the cost of recovering hydrogen from the purge. As gas permeation technology (and hydrogen permeation, in particular) is a very active R&D area, we hope that the results of this paper bring some attention to this novel (concentration driven) counter current application for gas permeation modules, apart from the presently more widespread (pressure driven) cross-flow application.